Microglia and neurogenesis in the epileptic dentate gyrus. Issue 1 (1st January 2016) - Luo, Cong; Ikegaya, Yuji; Koyama, Ryuta
ABSTRACT: Microglia are recognized as major immune cells in the brain. They have been traditionally studied in various contexts of disease, where their activation has been assumed to induce mostly detrimental effects. Recent studies, however, have challenged the current view of microglia, clarifying their essential contribution to the development of neural circuits and brain function. In this review, we particularly discuss the role of microglia as the major orchestrators that regulate adult neurogenesis in the hippocampus. We also review the roles of microglia in seizure-induced adult neurogenesis in the epileptic dentate gyrus. Specifically, we introduce our recent study, in which we identified a novel mechanism by which viable newborn cells in the adult dentate gyrus are phagocytosed and eliminated by microglia after status epilepticus, maintaining homeostasis of the dentate circuitry. This review aims to reconsider the microglial function in adult neurogenesis, especially when they are activated during epileptogenesis, challenging the dogma that microglia are harmful neurotoxic cells.